THE URGENCY OF RATIFICATION OF THE UNITED NATIONS CONVENTION AGAINST CYBERCRIME IN THE ERADICATION OF CRIMES RELATED TO ONLINE SEXUAL VIOLENCE AGAINST CHILDREN IN INDONESIA - Muhammad Haikal Bassam; Erlies Septiana Nurbani (Mataram Journal of International Law, 2026)
The threat of child sexual exploitation in the digital space is transnational and continues to increase, requiring the strengthening of a more progressive national legal framework. This study aims to analyze the limitations of national legal instruments in addressing online child sexual abuse crimes and to examine the urgency of ratifying the United Nations Convention against Cybercrime (UNCC) as a strategic step in combating these crimes. The research questions in this study focus on the regulation of child protection and the criminal liability of perpetrators of child sexual violence in current national law, as well as the significance of ratifying the UNCC in strengthening cross-border law enforcement jurisdiction. Using a doctrinal legal research method with a legislative, comparative, and case-based approach, the researcher mapped the norms of the ITE Law, the Child Protection Law, the TPKS Law, and international instruments such as the ICCPR, CRC, Budapest Convention, and UNCC. The results of the study show that national legal regulations are still sectoral, reactive-territorial, and have legal loopholes in criminalizing acts such as psychological manipulation carried out by perpetrators to build trust with children for the purpose of sexual violence (child grooming) and sexually violent material produced using technology (deepfake). In addition, dependence on bureaucratic Mutual Legal Assistance (MLA) procedures is a significant operational obstacle. In conclusion, the ratification of the UNCC is an urgent necessity to close the normative gap through the standardization of criminal acts (as in Articles 14 and 15) and the provision of a special (fast-track) access to digital evidence across jurisdictions in order to ensure maximum protection for Indonesian children in the global cyberspace.